Adequacy and tolerance to ass's milk in an Italian cohort of children with cow's milk allergy - Braccio Serena; Paglialunga Claudia; Tesse Riccardina; Armenio Lucio (BMC, 2009)
Abstract Background The therapy for cow's milk proteins allergy (CMPA) consists in eliminating cow's milk proteins (CMP) from the child's diet. Ass's milk (AM) has been recently considered as substitute of CMP. This prospective study investigated tolerance and nutritional adequacy of AM in children with CMPA from Southern Italy. Methods Thirty children (aged 6 months to 11 years) with suspected CMPA were enrolled. They underwent skin prick tests and bouble-blind, placebo controlled food challenge to CMP. After confirming the diagnosis of CMPA, patients received fresh AM in a open challenge. Specific serum CMP and AM IgE, and biochemical parameters in blood were also assessed. Auxological evaluations were performed in all subjects at entry (T0) and after 4-6 months (T1) of AM intake. Results Twenty-five children resulted elegible for the study, and 24 out of 25 subjects (96%) tolerated AM at the food challenge. Auxological data resulted improved by the end of the study in all patients, while blood biochemical parameters did not vary during the follow-up. Conclusion Our data confirm the high rate of AM tolerability in children with moderate symptoms of CMPA. Moreover, we found that AM seems to have nutritional adequacy in subjects with a varied diet.